The Magic of Presence: Moments, Memories, Methods - Sauter , Willmar (Nordic Theatre Studies, 2023)
Every habitual visitor remembers some magic moments of theatrical events: a striking feeling of immediate presence. What are these experiences of presence about? What triggers them, under which circumstances do they take place? This text is an attempt to point out some decisive parameters that facilitate strong experiences of performative situations. On the basis of a new rhombic model, I will show how these parameters coordinate the senses of the beholder and create magic moments of presence. Then, presence remains as future memories of the past.